Korsakoff's syndrome, cognition and clonidine. - O'Carroll, R; Moffoot, A; Ebmeier, K; Murray, C; Goodwin, G (1993)
Eighteen patients suffering from Alcoholic Korsakoff's Syndrome participated in a placebo-controlled double-blind cross-over trial of clonidine 0.3 mg b.d. for two weeks versus matched placebo for two weeks. A detailed neuropsychological assessment was carried out at the end of each treatment phase and staff ratings of behaviour were also obtained. Clonidine treatment resulted in no significant improvement over placebo on any of the cognitive measures employed. The results contradict previous smaller studies which had suggested that chronic treatment with clonidine had a memory-enhancing effect in Korsakoff's syndrome.